2023
DOI: 10.1038/s41598-023-32600-w
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for sequence-specific recognition of guide and target strands by the Archaeoglobus fulgidus Argonaute protein

Abstract: Argonaute (Ago) proteins are found in all three domains of life. The best-characterized group is eukaryotic Argonautes (eAgos). Being the structural core of RNA interference machinery, they use guide RNA molecules for RNA targeting. Prokaryotic Argonautes (pAgos) are more diverse, both in terms of structure (there are eAgo-like ‘long’ and truncated ‘short’ pAgos) and mechanism, as many pAgos are specific for DNA, not RNA guide and/or target strands. Some long pAgos act as antiviral defence systems. Their defen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 52 publications
4
4
0
Order By: Relevance
“…Subsequent analysis revealed that all proteins associate with short RNA molecules (the predominant length being ∼20–30 for, fAfAgo and scfAfAgo, and ∼15–25 nt for AfAgo) that contain a 5′-phosphate (Figure 2A and B ) and display a pronounced preference for the 5′-AU terminal dinucleotide (Figure 2B ). These findings are in line with our previous study, where we demonstrated that AfAgo preferentially uses gRNA to recognize complementary tDNA ( 21 ).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Subsequent analysis revealed that all proteins associate with short RNA molecules (the predominant length being ∼20–30 for, fAfAgo and scfAfAgo, and ∼15–25 nt for AfAgo) that contain a 5′-phosphate (Figure 2A and B ) and display a pronounced preference for the 5′-AU terminal dinucleotide (Figure 2B ). These findings are in line with our previous study, where we demonstrated that AfAgo preferentially uses gRNA to recognize complementary tDNA ( 21 ).…”
Section: Resultssupporting
confidence: 93%
“…We find that for both fAfAgo and scfAfAgo the optimal combination is an RNA guide and a complementary DNA target since all other guide-target combinations resulted in suboptimal target binding (Figure 3A ). In line with our previous results, AfAgo does not exhibit such clear selectivity, but its target binding is evidently weaker in comparison to fAfAgo and scfAfAgo ( 21 ). The affinity of all tested binary pAgo:gRNA complexes to DNA targets also depends on the guide:target sequence complementarity, as the low complementarity tDNA strands yielded no detectable ternary complexes (Figure 3B ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations